2007
DOI: 10.1016/j.ejheart.2006.11.004
|View full text |Cite
|
Sign up to set email alerts
|

NT‐proBNP levels and diastolic dysfunction in β‐Thalassaemia major patients

Abstract: Background: The early diagnosis and treatment of heart failure in β-thalassaemic patients is related to survival. Iron alone or in combination with other factors causes diastolic dysfunction, which usually precedes systolic dysfunction. NT-proBNP is a sensitive biomarker of ventricular dysfunction. Aim: To evaluate NT-proBNP in non heart failure β-thalassaemic patients. Methods: Fifty-two β-thalassaemia major patients (mean age: 27.2 ± 12.5 years) with normal LV systolic function, underwent NT-proBNP measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 30 publications
(36 reference statements)
6
44
0
2
Order By: Relevance
“…It has been shown recently that amino-terminal pro-B-type natriuretic peptide may be used as an early index of diastolic left ventricular dysfunction in patients with thalassemia major. 1 Indeed, amino-terminal pro-B-type natriuretic peptide was found to be increased in a group of 52 patients with thalassemia major with preserved left ventricular systolic function, compared with normal controls, and that increase was evident before the conventional Doppler indices of diastolic left ventricular function became abnormal. 1 In comparison with B-type natriuretic peptide, amino-terminal pro- The measures concern all patient categories.…”
Section: Therapeutic Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown recently that amino-terminal pro-B-type natriuretic peptide may be used as an early index of diastolic left ventricular dysfunction in patients with thalassemia major. 1 Indeed, amino-terminal pro-B-type natriuretic peptide was found to be increased in a group of 52 patients with thalassemia major with preserved left ventricular systolic function, compared with normal controls, and that increase was evident before the conventional Doppler indices of diastolic left ventricular function became abnormal. 1 In comparison with B-type natriuretic peptide, amino-terminal pro- The measures concern all patient categories.…”
Section: Therapeutic Issuesmentioning
confidence: 99%
“…1 Indeed, amino-terminal pro-B-type natriuretic peptide was found to be increased in a group of 52 patients with thalassemia major with preserved left ventricular systolic function, compared with normal controls, and that increase was evident before the conventional Doppler indices of diastolic left ventricular function became abnormal. 1 In comparison with B-type natriuretic peptide, amino-terminal pro- The measures concern all patient categories. ¶Combination regimens (oral and subcutaneous) or constant infusion (subcutaneous or intravenous).…”
Section: Therapeutic Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino-terminal pro-B-type natriuretic peptide may serve as an early index of diastolic LV dysfunction in patients with iron overload. 10 Indeed, it was shown that amino-terminal pro-B-type natriuretic peptide might be elevated in thalassemia major patients with preserved LVEF before conventional Doppler indices of diastolic function became abnormal 30 or when Doppler and tissue Doppler values were inconclusive. 31 CMR-derived T2* relaxation time is currently the mainstay for the quantitative assessment of cardiac iron deposition.…”
Section: Diagnosis and Screeningmentioning
confidence: 99%
“…30,31 If the cause of iron overload persists and no proper iron chelation therapy is initiated, the majority of patients with IOC develop LV remodeling that ultimately leads to LV dilatation and reduced LVEF, the so-called dilated phenotype of IOC. 10,32 In a minority of cases (Ͻ10%) characterized by severe iron overload, restrictive LV dysfunction leads, in advanced age, to the development of pulmonary hypertension, right ventricular dilatation, and right-sided heart failure without LV anatomic remodeling and with preserved LVEF, even at the final stages, the so-called restrictive phenotype.…”
Section: Kremastinos and Farmakis Iron Overload Cardiomyopathy 2255mentioning
confidence: 99%